2013
DOI: 10.1089/chi.2012.0147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Community-Based Weight Management Program for Predominantly Severely Obese, Difficult-To-Reach, Inner-City Minority Adolescents

Abstract: Abstract:Background: Few interventions targeting severely obese minority youth have been implemented in community-based settings. We evaluate a 9-month multicomponent, community-based program for obese, inner-city adolescents.Methods: Of 5250 estimated eligible adolescents, 349 were recruited; they had a mean age of 15 -2 years, mean BMI %ile 98.9 -1.5, and comprised 52% African American and 44% Hispanic. Longitudinal trends of anthropometric measures were compared 1 year before enrollment (T -12), at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Among African American and Hispanic or Latina women in this sample, only about one in five of the women who were originally recruited were retained at the primary outcome measurement endpoint, which is consistent with other randomized controlled trials in the behavioral and clinical sciences [12,14,19,46,47]. Also, similar to other studies, most participants dropped out early in the process, owing likely to both the complexity of behavior change and the efficacy of strategies employed herein to encourage drop out early in the study [48][49][50][51].…”
Section: Original Researchsupporting
confidence: 77%
See 1 more Smart Citation
“…Among African American and Hispanic or Latina women in this sample, only about one in five of the women who were originally recruited were retained at the primary outcome measurement endpoint, which is consistent with other randomized controlled trials in the behavioral and clinical sciences [12,14,19,46,47]. Also, similar to other studies, most participants dropped out early in the process, owing likely to both the complexity of behavior change and the efficacy of strategies employed herein to encourage drop out early in the study [48][49][50][51].…”
Section: Original Researchsupporting
confidence: 77%
“…Most studies report the number of people recruited, perhaps reporting recruitment ratios (number recruited/ number eligible or screened) [5,[18][19][20]. In contrast, very few studies report characteristics indicating the representativeness of the sample and whether the sample that was retained through completion of the study represented the sample that was recruited initially [21].…”
mentioning
confidence: 99%
“…Despite efforts to resolve barriers (e.g. transportation) for participation in interventions, adolescent adherence and engagement in clinic-based programs remain low (Rieder et al, 2013). Furthermore, because of the serious consequences for adult health, youth who exhibit glucose dysregulation should receive behavioral or pharmacological interventions as recommended by the American Diabetes Association (“Type 2 diabetes in children and adolescents.…”
Section: Obesity and Cardiometabolic Riskmentioning
confidence: 99%
“…Compared with their peers, children who adhere to recommendations are also more likely to come from higher‐income families and have parents with higher levels of education . Studies that examined proxy measures of treatment adherence, including programme completion, motivation to make lifestyle changes, and perceived barriers and support, have reported that (i) non‐completers (vs. completers) are more likely to be heavier , older, of ethnic minority, and with a lower income and (ii) children with obesity (vs. less obese children) are less ready as well as perceive more barriers and less support to make healthy lifestyle changes . Taken together, these findings suggest that children who are less likely to adhere to dietary and physical activity guidelines are more affected by or at a higher risk of obesity.…”
Section: The Adherence Paradox: Those For Whom Greater Adherence To Bmentioning
confidence: 99%